Profil Petani Pembudidaya Talas (Araceae ) di Desa Karang Intan Kabupaten Banjar, Kalimantan Selatan - Herlin Mardiana; Anang Kadarsah; Erma Agusliani (Universitas Lambung Mangkurat, 2023)
This study aims to analyze the density and distribution of the taro plant and to obtain information about the knowledge of the local population on the cultivation technique of taro (Colocasia esculenta L. Shoot) in Karang Intan Village, Banjar Regency, South Kalimantan. Taro cultivators was carried out by interview method with 10% of respondents. The interview were made a comparison percentage and discussed descriptively. The results showed that the taro cultivators are dominated by women (56.25%) and the rest 43.75% are men. Respondents majority were from the age group 41-50 years (43.75%) and the lowest (12.5%) was from the age group 21-30 and 31-40 years. Farmers are the most occupied livelihood (75%) and the rest are fish farmers (25%). Taro cultivators in Karang Intan Village still apply simple cultivation techniques and local wisdom that are hereditary. Key words: Taro, farmer, knowledge